Multi-dimensional creativity: a computational perspective. Issue 1 (2nd January 2016) - Sosa, Ricardo; Gero, John S.
Abstract : This paper presents a multi-dimensional perspective for the study of creativity and formulates a framework for computational creativity that enables the definition of functional relationships among scales, and captures the effects of time. Its relevance and usefulness are shown first by classifying recent studies of computational creativity and second by illustrating multi-dimensional approaches to the computational study of creativity with sample simulation scenarios. The paper closes offering modeling guidelines for the computational studies of creativity.